Shaping Rewards with Temporal Information to Guide Reinforcement Learning - Lundgren, Linus (My University, 2025)
Reinforcement learning (RL) methods that apply pretrained Vision-Language Models (VLMs) to compute rewards typically use a single observation of the environment to do so. This is problematic because any information emerging from the sequential nature of RL, i.e. temporal information, is therefore disregarded. This thesis explored how temporal information can be incorporated into the VLM reward computation, by first distinguishing between fixed and adaptive temporal information. In fixed temporal information, additional inputs are provided to describe the environment’s progression through time, but these inputs remain unchanging throughout each episode. In contrast, adaptive temporal methods take additional inputs that can change as the episode progresses. Positional and directional rewards were defined to take advantage of fixed and adaptive temporal information respectively, along with new supervised finetuning methods for the directional reward functions. Evaluated with a sample efficiency metric over 6 robotic manipulation tasks, the best new positional rewards performed 18.4% better than previous methods, while directional rewards performed 23.0% better. Combining positional and directional rewards showed a 25.4% improvement, which was the best performance achieved by any method in this thesis.
Keywords: VLM; reinforcement learning; machine learning; transfer learning; neural networks